2007
DOI: 10.1007/s11430-007-6025-y
|View full text |Cite
|
Sign up to set email alerts
|

Fission-track-age records of the Mesozoic tectonic-events in the southwest margin of the Ordos Basin, China

Abstract: Based on the analysis of apatite and zircon fission track (FT), the FT age distribution and the peck-ages of the Mesozoic tectonic events in the southwest margin of the Ordos Basin (OB) were discussed.(1) The early event mainly occurred at 213-194 Ma with a peck-age of 205 Ma, and corresponded to the tectonic uplift and the mega-clastic deposit in the southwest OB during the Late Triassic. (2) The middle event included at least two episodes. One was at 165-141 Ma with a peck-age of 150 Ma, and the other was at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Combined with the views of predecessors (Li, 2006;Yang & Dong, 2020;Zhang et al, 2020;Zhao, 2003), we think that the approximately E-Wtrending Dafosigou fold system was mainly formed during the Middle-Late Triassic, which is the same as the activity time of Xinjinggou thrust fault and Jijigou fold system. The zircon FT age of the WFTB shows that there was a significant erosion event in the Late Triassic, which suggests the existence of tectonic compression event in the Late Triassic (Chen et al, 2007).…”
Section: Two Mesozoic Contractional Events In the Weiningbeishan Fold...mentioning
confidence: 96%
See 1 more Smart Citation
“…Combined with the views of predecessors (Li, 2006;Yang & Dong, 2020;Zhang et al, 2020;Zhao, 2003), we think that the approximately E-Wtrending Dafosigou fold system was mainly formed during the Middle-Late Triassic, which is the same as the activity time of Xinjinggou thrust fault and Jijigou fold system. The zircon FT age of the WFTB shows that there was a significant erosion event in the Late Triassic, which suggests the existence of tectonic compression event in the Late Triassic (Chen et al, 2007).…”
Section: Two Mesozoic Contractional Events In the Weiningbeishan Fold...mentioning
confidence: 96%
“…Based on regional geological surveys and Google Earth images, we found that the folds formed in the Devonian strata in the eastern part of the WFTB are mainly E-Wtrending open folds (Figures 3 and 4a) with large interlimb angles, while the folds formed in the Carboniferous strata in the central part of the WFTB are mainly E-W-trending chevron folds (Figures 3 and 4b) with small interlimb angles. Previous researchers mainly focused on the tectonic evolution of the WFTB (Chen et al, 2007;Yang & Dong, 2020;Zhang et al, 2020;Zhang, Li, et al, 2009) In this article, based on the detailed geologic mapping and Google Earth image interpretation, we finely reveal the differential deformation between the Devonian and Carboniferous strata through structural analysis. Subsequently, we construct three cross-sections and constrain the magnitude of N-S shortening strains of the Upper Devonian Zhongning Formation (D 3 z) and Carboniferous strata, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The breaking up of the erosion surface indicates the beginning of the tectonic uplift (Coltorti & Ollier, 2000;Galadini, Messina, Giaccio, & Sposato, 2003), and the watershed of modern rivers commenced forming. The formation age of the watershed between the Weihe River and Taohe River has also been dated to~1.4 Ma by electron spin resonance (ESR; Figure 12; Zhang, 2006 is based on the paleochannel reconstruction (Figure 7), indicates that (Chen et al,2007;Chen et al, 2015;Clark et al,2010;Duvall et al,2013;Enkelmann et al,2006;Lin, 2009;Liu et al,2013;Song & Qian, 2013;Wang et al, 2011;Wang, 2014;Yang et al,2013;Zheng et al, 2004Zheng et al, ,2006…”
Section: Erosion Ratementioning
confidence: 99%
“…Among various thermochronology methods, apatite fission track (AFT) and (U-Th)/He dating (AHe) are often used to study hydrocarbon-bearing basins [37,38] due to their ability to recover the basin evolution temperature range • C) [39][40][41], which is close to the temperature of oil and gas generation [8,42]. Although low-temperature thermochronology methods have been applied in the Ordos Basin, there are still some shortcomings: one is that most previous studies used AFT [43,44], whereas AHe, which is a technology developed in recent years, has not been widely used in the Ordos Basin [36]; the other is that the southern part of the basin, especially the Weibei Uplift, has a relatively low level of research due to the lack of oil and gas discoveries in the early stage, and vitrinite reflectance [45,46] and bitumen reflectance [25,26] have mostly been used to reconstruct the thermal history of the region.…”
Section: Introductionmentioning
confidence: 99%